Antibacterial Activity Assay Of Ethanolic Extract Of Bulbs Sticky Taro (Colocasia esculenta) Use TLC-Bioautografi - Hibai, Achmad Rosyadi Yusuf; Herwin, Herwin; Kosman, Rachmat (Fakultas Farmasi UMI, 2015)
A research on antibacterial activity assay of sticky ethanolic extract from taro tuber (Colocasia esculenta) has been conducted in order to determine the antibacterial activity of ethanolic extract of the stem Colocasia esculenta against several assay bacteria use TLC-Bioautografi. Results of antibacterial activity screening showed that the ethanol extract of te Colocasia esculenta at a concentration of 1 mg/ml exhibited inhibitory activity against bacteria of Bacillus subtilis, Escherichia coli, Pseudomonas aerugginosa, Salmonella typhi, Shigella dysentriae, Staphylococcus aureus, Staphylococcus epidermidis, Streptococcus mutans, and Vibrio cholera. Test result showed by TLC-Bioautography using the eluent n-hexane : ethyl acetate (4:1) obtained Rf 0.38 value providing activity to Escherichia coli, Pseudomonas aerugginosa, Salmonella typhi, Shigella dysentriae, Staphylococcus aureus, Streptococcus mutans, and Vibrio cholera. The results of identification of active chemical component showed that the ethanolic extract of the stem of Colocasia esculenta on Rf 0.38 value was te alkaloid using dragendorf as the reagent.